Drivers of banks' cost of debt and long-term benefits of regulation - an empirical analysis based on EU banks - Artus Galiay; Laurent Maurin (European Central Bank (ECB), 2015)
Based on a sample of EU listed banks, we estimate the sensitivity of banks' marginal cost of debt and analyse the potential impact of the post-crisis regulatory package. We build synthetic estimates of risk in banks' books and the macroeconomic environment and argue that regulatory changes alter the transmission of these risks to banks' market funding costs. To circumvent the fact that new regulations are not observable, we also construct indices for each of the new regulatory packages, (1) capital and leverage, (2) liquidity and funding, and (3) banks' structural perimeter (which seeks to separate real economy lending form market activities). Those are based on the variables reported insample which are most correlated with the regulatory targets. We find evidence of a dampening effect of banks' capital base on the transmission of risks to market funding costs: a 1 standard deviation increase in the capital and leverage index reduces the transmission of a 1 standard deviation shock to macroeconomic risk by up to 20 basis points (bps). Based on a different sample and obtained from a different methodology, our results for capital are comparable to those of Babihuga and Spaltro (2014). We also find evidence of a dampening effect for funding and liquidity regulations, with a 1 standard deviation increase in the index reducing the transmission of a 1 standard deviation shock to macroeconomic risk by up to 34 bps. However, we do not reach a clear conclusion regarding the impact of structural perimeter regulations.
Keywords: G01; G21; 330; Bank balance sheet; bank funding costs; Bank structural perimeter; Basel III regulations; Capital and leverage; cross section estimates; CRR and CRD IV; dynamic estimates; factor based indices; Funding and liquidity; risk